Innovators, innovation and increasing returns to scale: Solving New Zealand’s productivity paradox - Hendy, Shaun; Sissons, Catriona (New Zealand Science Review, 2011)
​Using patents as a proxy, we examine New Zealand’s performance in innovation from the perspective of the economic geographer. By examining the regional distribution of patents in Australasia, we find that the number of patents per capita in Australasian cities scales superlinearly with city size. In fact, if one empirically corrects for city size, New Zealand cities appear to perform similarly to Australian cities on a per capita basis. We also find evidence for large networks of inventors in the patent literature, supporting the idea that connectivity promotes the generation of knowledge. These findings suggest that New Zealand’s poor innovation performance stems from both its small population and its low population density. To overcome these disadvantages, we suggest that New Zealand needs to learn to act like a city of four million people by connecting people and ideas thoughout the country.